Analisis Kausatif Bahasa Melayu Berdasarkan Korpus Menggunakan Pendekatan Minimalis. [PL5074. K48 2004 f rb] [Microfiche 7676] - Mohammad, Siti Khaotijah (2003)
A study of causative structure construction is a study of Malay sentences that have a causative verb in complex word form or sentences that have two verbs.